Electrical Isolation of Two Earthing Systems under Lightning Conditions with TiO2 Nano Fluid Barrier - Gomes C.; Izadi M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric equipment protection; Electrodes; Lightning; Lightning protection; Oxides; Soils; Titanium dioxide; Transients; Earthing electrodes; Electrical continuity; Electrical isolation; Laboratory experiments; Potential barriers; Potential gradients; Titanium dioxides (TiO2); Two-electrode systems; Electric grounding